Implementasi Kebijakan Sistem Manajemen Keselamatan Pelayaran (Studi Di PT. Maritim Barito Perkasa Banjarmasin) - M. Firdaus Suwestian; Saladin Ghalib; Setio Utomo (Universitas Lambung Mangkurat, 2015)
Implementation of ISM Code in PT. Maritim Barito Perkasa Banjarmasin intended to raise and maintain the safety culture in the operation of the vessel with the aim of preventing accidents that can cause loss of life, damage to the vessel and material losses. This study aims to determine the extent of the application of the ISM Code in the safety management operation of the vessel as vessel accident prevention efforts. Method approach used in this study is a qualitative approach. The results showed that the problems that arise in the implementation of the ISM code in PT. MBP is related to the ability of Human Resources knowledge in understanding and implementing ISM code, lack of supervision, especially in terms of enforcing regulations firmness felt ISM code is less strict, so that creates a culture of ignoring the rules that have been set by the company through the ISM code.Therefore it is necessary to improve human resource capacity, especially in terms of language mastery and competence of seamanship, increased support for companies, especially monitoring and increased coordination between the ship and the company in PT. MBP.